EPIDEMIC PROCESS IN MODERN CONDITIONS - E. D. Savilov (Acta Biomedica Scientifica, 2012)
Nowadays the evolution of epidemic process is under active influence of a new adjusting risk factor - technogenic environmental contamination. Negative influence of ecological pressure on manifestations of infectious diseases is realized in destabilization of epidemic process: significantly higher level of incidence, greater amplitude of its fluctuations around a trendline and. shortening cyclic componenta. Besides this, the more heavy clinical manifestations of infectious process and its longer duration with simultaneous development of the complications, accompanying diseases and. synchronization of process takes place. Decrease of immunological and epidemiological effectiveness of vaccination is also registered. This paper establishes, that the minimal period of infection incidence is the most vulnerable part in a uniform circuit of epidemic process. It is shown in epidemiological experiment that the complex of preventive actions at management of infection incidence is necessary for making active during a minimum level of development of epidemic process in its intraannual dynamics.